PENGABDIAN MASYARAKAT BAZNAS BANTEN DALAM MENINGKATKAN SUMBER DAYA MANUSIA MELALUI BEASISWA PROGRAM SATU KELUARGA SATU SARJANA - Itang Itang; Wazin Baihaqi (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
This study examines community service activities carried out by Baznas Banten in improving human resources through the One Family, One Scholar program. The One Family One Undergraduate Program provides opportunities and convenience for students to complete their undergraduate education at several universities in Banten with the assistance and collaboration with Baznas Banten. The efforts made by Baznas Banten in the One Family One Undergraduate Program are an effort to help the government in educating the life of the nation. The research method used in this study is to use a descriptive research method with a qualitative approach. From the results of the research carried out, it can be seen that the beneficiary families of the One Family One Undergraduate Program are very helped by the existence of the program, as evidenced by the number of beneficiary families who have finished college and become undergraduates, and even one of them has become an outstanding and best graduate student